2018
DOI: 10.1111/jon.12523
|View full text |Cite
|
Sign up to set email alerts
|

MP2RAGE and Susceptibility‐Weighted Imaging in Lesional Epilepsy at 7T

Abstract: MRI at ultra-high field is very promising for the detection of inconspicuous epileptogenic lesions and may facilitate epilepsy surgery of a great number of to-date MRI-negative patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…In a recent qualitative assessment in lesional epilepsy cases at 7 T, epileptogenic characteristics (cortical thickening, cortical–subcortical atrophy, and blurred GM–WM junction phenomena) were well appreciated on MP2RAGE images (6/7 cases = visual sensitivity 85.7%; Pittau et al, ). This is similar to our study, where MP2 (80%) and MP2 VBM variants showed a sensitivity between 80 and 100% in the lesional cohort ( n cases = 5).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a recent qualitative assessment in lesional epilepsy cases at 7 T, epileptogenic characteristics (cortical thickening, cortical–subcortical atrophy, and blurred GM–WM junction phenomena) were well appreciated on MP2RAGE images (6/7 cases = visual sensitivity 85.7%; Pittau et al, ). This is similar to our study, where MP2 (80%) and MP2 VBM variants showed a sensitivity between 80 and 100% in the lesional cohort ( n cases = 5).…”
Section: Discussionmentioning
confidence: 97%
“…The resultant images show enhanced contrast‐to‐noise ratio (especially GM–WM contrast), independent of T 2 *, proton density, B1 − , and reduced B1 + inhomogeneities. Thus, acquired images are, at least partially, corrected for image bias intrinsically and have been called “self‐bias corrected images.” Newer studies have shown promise of MP2RAGE in improving visualization of lesions (Beck et al, ; Pittau et al, ). Moreover, reduced intensity inhomogenities should also improve tissue segmentation, which facilitates VBM analysis for lesion detection (Ashburner & Friston, ).…”
Section: Introductionmentioning
confidence: 99%
“…Both sequences are usually performed in less than 5 minutes, and their impact would further improve with the use of higher field strengths of 3T and above. 2 The detection of a subtle lesion on SWI may also permit the performance of a timely epilepsy surgical procedure 3 in these patients, with a typically excellent outcome. Furthermore, new surgical techniques such as stereotactic laser ablation may allow for a safe and effective delivery of stereotactic therapy for epileptogenic cavernoma, especially for patients in whom open brain surgery presents a barrier to treatment.…”
Section: Susceptibility-weighted Imaging (Swi) or T2* Contrasts Shoulmentioning
confidence: 99%
“…Also among these modalities is susceptibility‐weighted imaging (SWI), which combines T2‐weighted magnitude and phase information at long echo time. While originally developed primarily for venography, taking advantage of the geometry and paramagnetic content of veins, SWI was soon found valuable for numerous other applications, including the detection of trauma, stroke, cortical dysplasia and tumors . At 7T, SWI has shown enhanced sensitivity in detecting multiple sclerosis lesions and features of polymicrogyria in epilepsy, for example.…”
Section: Introductionmentioning
confidence: 99%